2023
DOI: 10.11646/zootaxa.5340.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Annotated Checklist of Marine Amphipods (Crustacea: Amphipoda) of India

DIMPLE THACKER,
KRUPAL PATEL,
ALAN MYERS
et al.

Abstract: An annotated checklist of the marine amphipods recorded from Indian waters is compiled from the available peer-reviewed literature. A total of 266 species belonging to 133 genera and 56 families are listed. The maximum numbers of species were recorded from the South Indian Ecoregion (177 species, 98 genera, 47 families), followed by the Western India Ecoregion (101 species, 72 genera, 36 families), the Eastern Indian Ecoregion (99 species, 65 genera, 35 families), the Northern Bay of Bengal Ecoregion (92 speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 141 publications
0
0
0
Order By: Relevance
“…Extensive studies were conducted on various groups of crustaceans inhabiting the coastal areas of Gujarat State to understand their diversity ( Trivedi & Vachhrajani, 2013 , 2017 ; Trivedi, Soni & Vachhrajani, 2015 ; Trivedi, Osawa & Vachhrajani, 2016 ; Trivedi, Trivedi & Vachharajani, 2017 ; Trivedi, Campos & Vachhrajani, 2018 ; Trivedi et al, 2015a , 2015b , 2018 , 2020 ; Patel et al, 2022 ; Thacker et al, 2023 ) and ecology ( Trivedi, 2016 ; Trivedi & Vachhrajani, 2012 ; Trivedi & Vachhrajani, 2014a , 2014b ). Among these, crabs are widely distributed omnivores that are sensitive to environmental changes and frequently employed as pollution indicators ( Aheto et al, 2011 ; Jonah et al, 2015 ; Doshi et al, 2024 ).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies were conducted on various groups of crustaceans inhabiting the coastal areas of Gujarat State to understand their diversity ( Trivedi & Vachhrajani, 2013 , 2017 ; Trivedi, Soni & Vachhrajani, 2015 ; Trivedi, Osawa & Vachhrajani, 2016 ; Trivedi, Trivedi & Vachharajani, 2017 ; Trivedi, Campos & Vachhrajani, 2018 ; Trivedi et al, 2015a , 2015b , 2018 , 2020 ; Patel et al, 2022 ; Thacker et al, 2023 ) and ecology ( Trivedi, 2016 ; Trivedi & Vachhrajani, 2012 ; Trivedi & Vachhrajani, 2014a , 2014b ). Among these, crabs are widely distributed omnivores that are sensitive to environmental changes and frequently employed as pollution indicators ( Aheto et al, 2011 ; Jonah et al, 2015 ; Doshi et al, 2024 ).…”
Section: Introductionmentioning
confidence: 99%
“…The overall crab production of Gujarat was reported at around 179.60 million tonnes during 2007-2020 (179.60 million tonnes). Different groups of crustaceans occurring in the coastal areas of Gujarat State were studied extensively for their diversity (Trivedi and Vachhrajani, 2013;Trivedi et al, 2015a;Trivedi et al, 2015b;Trivedi et al, 2015c;Trivedi et al, 2016;Trivedi and Vachhrajani, 2017;Trivedi et al, 2018a;Trivedi et al, 2018b;Trivedi et al, 2020;Patel et al, 2022;Thacker et al, 2023) and ecology (Trivedi and Vachhrajani, 2012;Trivedi and Vachhrajani, 2014a;Trivedi and Vachhrajani, 2014b;Trivedi, 2016). According to Gosavi et al (2021), 163 brachyuran crab species have been found in coastal regions of Gujarat.…”
Section: Introductionmentioning
confidence: 99%